Laser cladding materials-process-performance-investigation - Chew, Youxiang (2016)
Laser cladding is an additive manufacturing process that is used for surface repair and restoration applications in many industries such as in aerospace, marine and transport sections. In this study, modelling of residual stress from laser cladding process, fatigue performance testing and fatigue life prediction analysis is reported. AISI 4340 steel substrate-clad pair system was selected for this investigation as it is widely used in relevant applications discussed. In this work, clad specimens were fabricated, cut, polished and etched for microstructure observation and micro-hardness indentation studies to characterize clad to substrate material properties. A framework for fatigue performance characterization of laser clad specimens is presented in this study. Five types of laser clad specimens were designed for fatigue tests to characterize the fatigue failure behavior of laser clad AISI 4340 steel powder on steel substrate and compared to 4340 substrate fatigue S-N curve results. Type I specimen is designed to characterize fatigue failure behavior from the clad weld toe region of as-clad specimens. A significant reduction in fatigue performance for Type I specimen was observed due to failure from clad-toe features. Type II and Type III specimen designs investigate the feasibility of using pre and post-clad machining operations to improve fatigue strength. Type IV specimen design is used to characterize clad specimens with extended clad surface area. The post-clad ground specimen show significant improvement in fatigue strength. Type V specimen design with post-clad heat-treatment is able to recover fatigue strength back to comparable level with the unclad substrate material S-N curve performances. A three dimensional finite element (FE) model was developed to simulate residual stress induced from laser cladding of AISI 4340 steel. A laser power attenuation model was proposed for the laser-powder-interaction zone under the coaxial powder feeding nozzle. The thermal analysis integrated the deposition of clad beads with laser heat input. This was implemented using user-defined subroutines to thermally activate clad element conductivity and surface heat transfer film conditions simultaneously with the attenuated laser heat flux. The FE model was subsequently applied to simulate cladding of 10 clad beads over an area to study the effects of depositing multiple successive clad beads on residual stress field. Fractured surface of Type I as-clad specimen show that multiple surface cracks initiate from the clad-toe region due to clad bead overlap features deposited in a raster scan pattern. A fatigue crack growth modeling algorithm capturing the observed fatigue behavior of periodic multiple co-planar semi-elliptical cracks initiating from these features was developed based on crack closure concepts for small cracks to predict the fatigue S-N curve.